2020
DOI: 10.1111/ijcp.13845
|View full text |Cite
|
Sign up to set email alerts
|

The association of serum uric acid with metabolic syndrome and its components—From a single‐clinical centre in China

Abstract: Background and Objectives Increasing evidence suggests that uric acid (UA) levels may play a role in the MetS. The purpose of this study was the association of serum uric acid with metabolic syndrome and its components from a single‐clinical centre in China. Subjects and Methods We retrospectively analysed the physical examination information of patients at the Health Checkup Centre of the Beijing Friendship Hospital, Capital Medical University in 2018. MetS was defined as ≥3 of the risk factors according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
7
2
Order By: Relevance
“…We identified that SUA levels were positively correlated with 1hCp, 2hCp, and the Hyperuricemic patients were older and had higher values of macroalbuminuria, BMI, TC, C-peptide, the prevalence of hypertension, and MetS, but lower values of HDL-c and HbA1c [11]. SUA was also strongly associated with full MetS as well as hypertriglyceridemia [22,23]. Nevertheless, some prospective and retrospective studies have yielded contrary results.…”
Section: Discussionmentioning
confidence: 92%
“…We identified that SUA levels were positively correlated with 1hCp, 2hCp, and the Hyperuricemic patients were older and had higher values of macroalbuminuria, BMI, TC, C-peptide, the prevalence of hypertension, and MetS, but lower values of HDL-c and HbA1c [11]. SUA was also strongly associated with full MetS as well as hypertriglyceridemia [22,23]. Nevertheless, some prospective and retrospective studies have yielded contrary results.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, a meta-analysis of 11 prospective studies indicates an independent and linear dose-dependent relationship between HUA and MetS (Biradar et al, 2020). The HUA is closely associated with the MetS and its components (Borges et al, 2010;Thottam et al, 2017;Zhang et al, 2018;Xu et al, 2021). Here, we showed by the univariate analysis that the BMI, HC, WC, and TG were higher in the HUA subjects than those in the normal individuals, while the HDL-C level, a protective factor for CVD risk, was lower in the HUA group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorders may play a mediating role in the relationship between UA level and NAFLD outcome. Numerous studies have indicated that increased UA levels are associated with metabolic syndrome 12 , CVD 13 , hypertension 14 , type 2 diabetes 15 , and hypertriglyceridemia 16 . The underlying mechanism among high UA levels, NAFLD, and metabolic syndrome may be insulin resistance caused by hyperuricaemia.…”
Section: Discussionmentioning
confidence: 99%